Grinding of composite cores using diamond burs with different grit sizes - Vinicius Felipe Wandscher; Ana Maria Estivalete Marchionatti; Damiano Lodi Giuliani; Roberto Scotti; Paolo Baldissara; Luiz Felipe Valandro (Universidade Estadual de Campinas, 2020)
Aim: To evaluate the retention of Y-TZP crowns cemented in aged composite cores ground with burs of different grit sizes. Methods: Sixty composite resin simplified full-crown preparations were scanned, while 60 Y-TZP crowns with occlusal retentions were milled. The composite preparations were stored for 120 days (wet environment-37°C) and randomly distributed into three groups (n=20) according to the type of composite core surface treatment. The groups were defined as: CTRL (control: No treatment), EFB (extra-fine diamond bur [25μm]), and CB (coarse diamond bur [107μm]). The grinding was performed with an adapted surveyor standardizing the speed and pressure of the grinding. The intaglio surfaces on the crowns were air-abraded with silica-coated alumina particles (30 μm) and then a silane was applied. The crowns were cemented with self-adhesive resin cement, thermocycled (12,000 cycles; 5/55°C), stored (120 days) and submitted to a retention test (0.5mm/min). The retentive strength data (MPa) were analyzed using one-way analysis of variance and Tukey test, as well as Weibull analysis. Failures were classified as 50C (above 50% of cement in the crown), 50S (above 50% of cement in the substrate) and COE (composite core cohesive failure). Results: No statistical difference was observed among the retention values (p=0.975). However, a higher Weibull modulus was observed in the CTRL group. The predominant type of failure was 50S (above 50% of cement in the substrate composite). Conclusion: The retention of zirconia crowns was not affected by grinding using diamond burs with different grit sizes (coarse/extra-fine) or when no grinding was performed.